Dynamic Eyelid Reanimation in Facial Paralysis: A Systematic Review of Techniques and Outcomes - Ghanem Aljassem, MD; Zaki Alyazji, MD; Rami Misk, MD; Bara Shraim, MD; Mohamed Badie Ahmed, MD; Salim Al lahham, MD; Abeer Alsherawi, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Facial nerve palsy has severe morbidity, stemming from the loss of facial animation. Earlier attempts to restore eyelid function relied on static procedures. With the advancement in microsurgery techniques in recent years, dynamic eyelid reconstruction has gained more popularity. The goal is to maximize functional and aesthetic outcomes. This article aimed to highlight the current techniques and outcomes of dynamic eyelid reanimation. Methods:. MEDLINE, PubMed, PubMed Central, and Cochrane databases were searched. The included articles were reviewed. The techniques, methods of assessment, and associated outcomes were extracted and compared. Results:. Seventeen articles were included in the study. Tools used for assessment were diverse, including specific scales, questionnaires, and clinical examination. Techniques used were classified as nerve and muscle transfers. Nerve transfers included cross-facial nerve graft, nerve to masseter, and hypoglossal nerve transfer. Better results and lower morbidity were achieved with the combination of methods. Muscle transfers included free platysma muscle transfer as a free flap or graft, differentiated innervated gracilis muscle transfer, contralateral orbicularis oculi muscle, and temporalis muscle transfer. Better results were achieved with platysma-free functional muscle transfer. Conclusions:. Dynamic reanimation has better results than static procedures, and a combination of dynamic and static procedures might have the best results. The chosen method must be individualized, with the choice mainly affected by denervation time and the age of the patient.